Human rights: between crisis of legality and digital future. The relational justice approach as a proposal - Salas-Porras, María (My University, 2017)
Propuestas de contribuciones para afrontar los desafíos que se presentan a la ordenacion y fomento de los derechos humanos
Keywords: Derechos humanos - Congresos; Human rights; Challenges; Digital future; Crisis of legality; Relational justice